THE The Analysis of Religious Elements in The Unholy Movie Directed by Evan Spiliotopoulus: Sociological Approach - Dendi Saputra; Maria Ramasari; Agus Triyogo (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
The objective of this research was to describe what were the religious elements in The Unholy movie directed by Evan Spiliotopoulus. The method applied in this research was designed in qualitative descriptive. This research used human instrument by himself. The data was analyzed by describing the elements of religion in a movie. In collecting the data, the researcher watched The Unholy movie and in analyzing the data the researcher identifying four religion elements according to Rees theory. Based on the result of data analysis, the researcher found out data that: The first element of religion was God (s) and forces in the public square were Jesus Christ as God and Mary as mother of God with 7 scenes found. The second element was sacred symbols (re) defining what was real were eight syimbols; Jesus Bible, Banfield Shrine, Jesus Statue, Mary Statue, Church, Cross necklace, Holy fire and touched of forehead, then both of shoulders with fingers and clench both of hands into fists with 8 scenes found. The third element was sacred stories connecting past, present and future were 3 traditions or sacred stories from this movie, Mass, story of baby doll Kern and the feast of immaculate conception with 3 scenes found. The last element was a community worshiping and acting together was Catholic with 2 scenes found. Therefore, the researcher found 20 scenes in The Unholy movie that related to the religius elements based on Rees’s theory (2017). In conlusion, the religion elements in The Unholy movie included belief, attitude and action in everyday life.